2016
DOI: 10.1136/bmjopen-2016-011410
|View full text |Cite
|
Sign up to set email alerts
|

Social and behavioural factors associated with frailty trajectories in a population-based cohort of older adults

Abstract: ObjectiveThe goal of this study was to identify distinct frailty trajectories (clusters of individuals following a similar progression of frailty over time) in an ageing population and to determine social and behavioural factors associated with frailty trajectories.DesignPopulation-based cohort study.SettingOlmsted County, Minnesota.ParticipantsOlmsted County, Minnesota residents aged 60–89 in 2005.Primary outcome measureChanges in frailty over an 8-year period from 2005 to 2012, measured by constructing a yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 40 publications
9
59
1
3
Order By: Relevance
“…Interestingly, the associations between education, income and frailty disappeared in the group of aged ≥77 years. The age difference was also found in a population‐based cohort of older adults from the USA . It is also surprising that smoking and alcohol consumption have inverse associations with frailty, which was also found in previous studies .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, the associations between education, income and frailty disappeared in the group of aged ≥77 years. The age difference was also found in a population‐based cohort of older adults from the USA . It is also surprising that smoking and alcohol consumption have inverse associations with frailty, which was also found in previous studies .…”
Section: Discussionsupporting
confidence: 80%
“…Sociodemographic characteristics are also important for frailty. For example, sex, education, marriage status, income, smoking and alcohol drinking were reported to be associated with frailty in previous studies . However, such research findings were inconsistent with different published works, with education, smoking and alcohol drinking not being associated with frailty in some studies .…”
Section: Introductionmentioning
confidence: 72%
“…Tobacco consumption was a determining factor for the present study's sample, and it explains the environmental association through an OR of 2.72 (95% CI 1.13–6.53; data not shown), an opposite result from the study of the Dutch population (OR 0.73, 95% CI 0.43–1.03), but similar to that which was reported in the USA (OR 3.31, 95% CI 1.33–8.27) . Tobacco consumption is highly harmful for general health, due to the great number of chemicals and traces of highly reactive compounds that when assimilated into an organism can generate inflammatory processes, by which reactive oxygen species are released, which in turn generates oxidative stress, affecting telomere shortening .…”
Section: Discussionsupporting
confidence: 79%
“…An important factor that could explain this association is the role of socio‐economic factors in both frailty and oral health. Previous studies found that older adults with less education were more frail compared to those with better education . This was also observed when neighbourhood socio‐economic characteristics were used .…”
Section: Discussionmentioning
confidence: 61%